Separation of Different Contributions to the Total X-ray Luminosity in Gamma-ray Loud Blazars - Fan, Jun Hui (2005)
The relativistic beaming model has been successfully used to explain many of the observational properties of active galactic nuclei. In this model the total emission is formed by two components, one beamed, one unbeamed. However, the exact contribution from each component in unresolved sources is still not clear. In the radio band, the core and extended emissions are clearly separated. We adopt the method proposed by Kembhavi to separate the two contributions in the X-ray emissions in a sample of 19 gamma-ray loud blazars. It is clearly shown that the beamed emission dominates the X-ray flux and the unbeamed X-ray emission is correlated with the extended radio emission of the considered objects. We also find that the ratio of the beamed to the unbeamed X-ray luminosity is correlated with the X-ray spectral index, an effect that should be a consequence of the underlying X-ray emission mechanism.